PERAN MA’HAD AL-ZAYTUN DALAM IMPLEMENTASI LAGU INDONESIA RAYA MENURUT UNDANG-UNDANG NOMOR 20 TAHUN 2003 DAN MAQASHID SYARIAH - Haritsah, Haritsah; Ngainnur Rohmah, Siti; Rahim, Abdur (Cahaya Ilmu Bangsa, 2024)
Currently, numerous issues related to morality, values, and character among the younger generation are prevalent in society. This phenomenon is caused by the decline in noble national values and the erosion of nationalism and patriotism within the community. The Indonesian national anthem,